Pendengar dan Pelaku Firman Tuhan Berdasarkan Yakobus 1:19-27 dan Aplikasinya pada Orang Kristen Masa Kini - Setulus Hati Laia; Abad Jaya Zega (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Nowadays, there are many Christians who only listen to God's word but do not do it or who are said to be more concerned with their fleshly desires, one of which is: slandering fellow humans, rather than doing what God wants them to do. This article aims to explore the meaning of the writing in the letter of James about hearing and doing the word of God. This research uses a qualitative approach, by analyzing various sources such as books, novels, and updates related to the topic of this article. The results of the analysis see the importance of a servant of God interpreting the call to serve God for a positive impact on Christians today. A servant of God must be a blessing and an example in all aspects of life so that the congregation truly becomes a listener and doer of God's word and also believes that there is a God. The contents of this article are presented to make readers aware, especially God's servants, to serve God wholeheartedly and be role models for the congregation, not with other motivations but for the glory of God in enriching themselves to be true and good listeners and doers of God's word.